1998
DOI: 10.1095/biolreprod58.3.670
|View full text |Cite
|
Sign up to set email alerts
|

Protein C Inhibitor May Modulate Human Sperm-Oocyte Interactions1

Abstract: Protein C inhibitor (PCI) is a heparin-binding plasma serine protease inhibitor that was originally identified as an inhibitor of activated protein C. PCI has a broad protease specificity, inhibiting several proteases in hemostasis and fibrinolysis by acting as a suicide substrate. Recently it has been reported that proteases of the reproductive system, such as acrosin, prostate-specific antigen, and tissue kallikrein, can also be effectively inhibited by PCI. However, a direct relation between PCI and physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 24 publications
3
30
1
Order By: Relevance
“…8C-H), and could not be detected at 40 min (Fig.8I, J). Our results are similar to those observed with HongrES1 and Protein C Inhibitor; the expression of these two serpins were shown to be reduced during the AR (Elisen et al, 1998;Ni et al, 2009). Therefore, Esserpin-3 may control the AR process in E. sinensis in a manner similar to HongrES1 and Protein C Inhibitor as a decapacitation factor.…”
Section: Distribution Of the Esserpin-3 Protein In E Sinensissupporting
confidence: 88%
See 1 more Smart Citation
“…8C-H), and could not be detected at 40 min (Fig.8I, J). Our results are similar to those observed with HongrES1 and Protein C Inhibitor; the expression of these two serpins were shown to be reduced during the AR (Elisen et al, 1998;Ni et al, 2009). Therefore, Esserpin-3 may control the AR process in E. sinensis in a manner similar to HongrES1 and Protein C Inhibitor as a decapacitation factor.…”
Section: Distribution Of the Esserpin-3 Protein In E Sinensissupporting
confidence: 88%
“…For example, Protein C Inhibitor, a serpin protein secreted into the seminal fluid, can protect sperm, and is depleted during the acrosome reaction (AR) (Elisen et al, 1998). In murine, serpin2 binds to epididymal sperm and may block fertilization by inhibiting sperm capacitation and preventing sperm binding to the egg (Lu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has also been suggested that PCI bound to seminal coagula might control their liquefaction by inhibiting proteolytic degradation of semenogelin I and II by PSA (33). Others (7,34) and we (35) have shown that PCI interferes with sperm-egg binding and with in vitro fertilization, possibly due to its ability to inhibit the sperm protease acrosin (7,8). However, here too the in vivo relevance of these in vitro findings is questionable, since homozygous male mice with targeted disruption of the acrosin gene are fertile (36).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were allowed to liquefy at room temperature for 2 h. Semen was diluted to 15 ϫ 10 6 cells/ml in saline medium containing 137 mM NaCl, 2.5 mM KCl, 10 mM glucose, and 20 mM Hepes (pH 7.4) and washed through isotonic Percoll as described previously [10]. Washed spermatozoa were diluted up to 10 7 cells/ml in Hepes-buffered Tyrode medium (HBT-control: 120 mM NaCl, 21 The HTF-control was also isotonically supplemented with 24 mM bicarbonate (HTF-Bic) [22].…”
Section: Sperm Incubationsmentioning
confidence: 99%